English as an international language: perceptions of EFL preservice teachers in higher education institutions in Indonesia - Patuan Raja; Flora; Putrawan, Gede Eka; Razali, Abu Bakar (Hindawi, 2022)
It is widely known that the English language has rapidly spread across the globe and is now used for a wide range of purposes. Its status as a national/foreign language has shifted to that of an international language. Despite this awareness, however, studies on perceptions of English as an international language (EIL) among EFL preservice teachers in the Indonesian context are not commonplace in the literature. Therefore, this study was aimed at elucidating the perceptions of the four aspects of EIL among EFL preservice teachers in higher education institutions in Indonesia. This quantitative study adopted a descriptive approach using a five-point Likert scale questionnaire with a total of 14 close-ended statements. Data collected from the questionnaire were analysed using descriptive statistics. The findings suggest that EIL is positively viewed by participants as a means of global communication to achieve a variety of purposes. They welcome and accept various varieties of English, demonstrating a strong multilingual/multicultural understanding through their ability to accept different pronunciation patterns and adapt their behavior and conversational styles when interacting with people from diverse cultural backgrounds. They have a strong sense of ownership over their own English varieties. Finally, the study’s implications for the four aspects of EIL including the current status of English, English varieties, multicultural communication strategies, and the identity of English speakers are also discussed, along with limitations and recommendations for future research.